Dental Anomalies in Consanguineous Marriage: A Clinical-Radiological Study - Nuray Bağcı; Umut Pamukçu; Bülent Altunkaynak; İlkay Peker (Elsevier, 2022)
Objective: This study aimed to evaluate nonsyndromic developmental dental anomalies (DDAs) in individuals born from consanguineous and nonconsanguineous marriages and the possible effects of these marriages on self-reported systemic diseases. Methods: The study comprised a total of 880 patients aged 16 years or older who applied to our clinic for various dental problems. Based on detailed anamnesis, the patients were divided into 2 groups: individuals born from consanguineous (study group, n = 445) and nonconsanguineous (control group, n = 435) marriages. The parents' consanguinity type was also recorded, as well as the presence of any self-reported systemic diseases. The number, size, erupted, and morphological DDA types were investigated with both clinical and radiological examinations. All data from the 2 groups were recorded, and a statistical analysis was performed. Results: There was a statistically significant relationship between the consanguineous marriage and the size (microdontia), and morphological (dilaceration and taurodontism) DDA types. Additionally, a significant relationship was found between consanguineous marriage and self-reported systemic disease but not between the parents' consanguinity type and systemic disease. Conclusion: The results of this study suggest that consanguineous marriage affects DDAs.